Mating system, mate choice and parental care in a bark beetle. Issue 5 (6th April 2017) - Baruch, O.; Mendel, Z.; Scharf, I.; Harari, A. R
Abstract: The cypress bark beetle, Phloeosinus armatus, is a common element of the dying cypress tree system in East-Mediterranean countries. Adult beetles congregate for breeding on this ephemeral resource. We studied three traits that characterize this beetle's sexual behavior and linked them to its reproductive success: mating system, mate choice, and parental care. We found that the females are the 'pioneering sex', excavating the mating chamber. The average female is slightly larger than the male, and female and male body size is correlated, demonstrating size-assortative mating. The time it takes for a male to enter the mating chamber is positively correlated with female size and negatively correlated with its own size, which is perhaps responsible for this assortative mating. Males remain in the gallery during the period of oviposition, gradually leaving soon after the eggs hatch. The number of eggs laid and tunnel length are positively correlated with male body size. Finally, in the presence of both parents, more eggs are laid than when the female alone is present, demonstrating the important contribution of biparental care for reproductive success. We suggest that the interaction between a monogamous mating system, assortative mating, and biparental care contributes to reproductive success.